Gendered Learning in Islamic Education: A Systematic Review of the Effect of Audio-Visual Media on Female Students’ Fiqh Learning Outcomes in Indonesia - Milis Amelia Putri; Rapiko (Women, Education, and Social Welfare, 2026)
This study systematically reviews the effect of audio-visual media on female students’ Fiqh learning outcomes in Indonesian Islamic education. The study was motivated by the growing use of instructional video, animation, interactive multimedia, and AI-assisted video in Fiqh learning, while gender-specific evidence remains limited. Using PRISMA 2020, 18 studies published between 2015 and 2026 were selected and analyzed through a systematic narrative synthesis. The findings show that audio-visual media generally supports students’ cognitive achievement, motivation, engagement, and procedural understanding, especially in Fiqh topics that require demonstration, sequencing, and repeated observation, such as prayer, purification, and worship practices. However, most studies still discuss students as a general group and rarely report female students’ learning outcomes separately. This limits the understanding of how audio-visual media specifically supports female students’ religious learning experiences. This study contributes by highlighting the need for gender-responsive audio-visual Fiqh pedagogy that pays greater attention to female students’ procedural confidence, reflective understanding, and religious agency.